Progression of deformation and sedimentation in the southernmost Andes - Ghiglione, Matias (2005)
The chronology of thrust motion in the Fuegian thin-skinned fold-thrust belt was established using data from the Atlantic coast of Tierra del Fuego. A set of original structural-geological maps showing the distribution of structures, unconformities and synorogenic sequences in the last tip of the Andes reveals the cratonward propagation of thrusts and sedimentary depocenters. A succession of syntectonic angular and progressive unconformities occur in the studied zone: (1) an angular unconformity between Danian and Late Paleocene sequences, (2) a series of progressive and syntectonic angular unconformities developed from the Late Early Eocene to the Late Eocene, and (3) a Lower Miocene syntectonic unconformity. Additional evidence for the time-space location of the thrust-front is provided by the presence of seismically triggered sand intrusions in Late Cretaceous, Late Paleocene and Middle Miocene sequences. The integration of data shows that faulting occurred in three main episodes: San Vicente thrusting, ca. 61-55 Ma, Río Bueno thrusting, ca. 49-34, and Punta Gruesa strike-slip event, ca. 24-16 Ma. San Vicente thrusting represents the onset of thrust propagation onto the foreland craton. The thrust-front endured a major cratonward migration through the Río Bueno thrusting, and remained steady afterward. Punta Gruesa constitutes a strike-slip event, associated with the phase of wrench deformation that influences the southernmost Andes since the Oligocene. Although the overall pattern of faulting was progressively younger cratonward, several episodes of out-of-sequence thrusting and folding occurred. Other features in the southernmost Andes can be linked to these three deformation events to broadly characterize the behavior of the Fuegian orogenic wedge in terms of critical taper models. The Fuegian Andes underwent at least three cycles between subcritical, critical and supercritical stages of behavior in terms of deformation, erosion, and sedimentation.